Analysis of trehalulose in kelulut honey samples via HPLC-MS - J., Arif Zaidi; Zawawi, N.; Ramlan, N. A. F. M.; S., Nor Fadhilah (Rynnye Lyan Resources, 2023)
Over recent years, there had been many studies by Malaysian researchers focusing on kelulut (stingless bee) honey chemical profile. One of the ultimate purposes of carrying out the chemical profiling activity was to search for suitable unique biomarkers that can be used as quality as well as authenticity indicators. Both aspects are crucial in order to maintain the premium status of kelulut honey as it has always been regarded as one of the best multifunctional local health supplements. An interesting finding on a chemical component of kelulut honey was recently published. Trehalulose was identified as a major component in kelulut honey sourced from both Geniotrigona thoracica and Heterotrigona itama which are common species in Malaysian stingless bee farms. Since trehalulose is not commonly available from other natural sources, it can be a good quality marker candidate. To qualify as a good quality marker, a biochemical component must fulfil some criteria. This article reports on the potential of trehalulose as a quality indicator or marker in H. itama honey. Our preliminary studies focused on the analytical aspect of trehalulose based on analysis using high-performance liquid chromatography (HPLC) with evaporative light scattering detection (ELSD). Our findings showed that all kelulut honey samples collected contained trehalulose and the HPLC analysis can be carried out using a simple method provided that a pure commercial standard is available.